Complement in Pancreatic Disease—Perpetrator or Savior? - Bettac, Lucas; Denk, Stephanie; Seufferlein, Thomas; Huber-Lang, Markus (Frontiers in Immunology, 2017)
The complement system is a major pillar of the humoral innate immune system. As a first line of defense against pathogens, it mediates early inflammatory response and links different branches of humoral and cellular immunity. Disorders affecting the exocrine pancreas, such as acute pancreatitis, potentially lead to a life-threatening systemic inflammatory response with aberrant activation of complement and coagulation cascades. Pancreatic proteases can activate key effectors of the complement system, which in turn drive local and systemic inflammation. Beyond that, the extent of pancreas-complement interaction covers complex pro- and anti-inflammatory mechanisms, which to this day remain to be fully elucidated. This review provides a comprehensive overview of the pathophysiological role of complement in diseases of the exocrine pancreas, based on existing experimental and clinical data. Participation of complement in acute and chronic pancreatitis is addressed, as well as its role in tumor immunology. Therapeutic strategies targeting complement in these diseases have long been proposed, but have not yet arrived in the clinical setting.